Panorama da produção científica sobre educação hospitalar em programas de pós-graduação no Brasil - Pereira, Roger Trindade (Universidade Federal do Tocantins, 2020)
From the knowledge panorama mode, this assignment aimed to know the thematic and methodological trends, as well as the main results of the Brazilian research in the context of Hospital Education. Methodologically, it consists of an exploratory and descriptive proposal through a qualitative approach. The methodological procedures followed the path of bibliographic research in the context of the production of knowledge whose technique of results‟ treatment occurred through content analysis. To this end, initially a bibliographic survey of theses and dissertations defended in Brazil, from 2008 to 2017, was gathered at the Brazilian Digital Library of Dissertations and Theses. As a result of the bibliographic corpus composition, 79 researches were selected, having 14 theses and 65 dissertations as content of analysis. From the content analysis, emerged 8 a priori thematic subcategories and 20 a posteriori subthemes inferred in the process of exploration and interpretation of theses and dissertations. The results indicated a disparity in production in relation to geographic regions where theses and dissertations are developed, as well as a participation of 28 higher education institutions (IES) and 45 postgraduate programs, the main ones being: Education (73,40 %), Health (17.72%), others (8.88%), with predominantly 23 public HEIs (82.14%), also accounting for 82% of the period‟s total production. The main thematic trends of the research field were: Public Policies in Hospital Education; Human Development, Education and Humanization in Hospitals; Pedagogical Practices and Didactic-Curricular Organization; Home Pedagogical Care; Pedagogical Organization and Administrative Operation; Digital Information and Communication Technologies (ICTs); Teacher Training; Correlation between Education and Health in Hospitalization. In the methodological aspects, it is observed a predominant pattern of qualitative research approach, highlighting the main methodological methods of case study, field research and action research. Regarding the main results for the research field, it is identified a presence of isolated and disjointed investigations as a result of initiatives without evidence capable of demonstrating some continuity and expansion as to make this field an object of study more approached and systematic in postgraduate programs in the country.